Optimalisasi Pendidikan Anak TKI Di Sabah Malaysia - Arina, Nur; Gumilar, Gun Gun; Febriantin, Kariena (Innovative: Journal Of Social Science Research, 2025)
Education is a basic right of every citizen guaranteed in the 1945 Constitution. However, the reality is that there are still many children of Indonesian migrant workers (TKI) in Sabah, Malaysia, who have not gained access to proper education. Factors such as citizenship status, remote location, lack of infrastructure, and limited regulations hinder the fulfillment of their educational rights. To overcome these problems, the Indonesian government has established Sekolah Indonesia Kota Kinabalu (SIKK) and the Community Learning Center (CLC) as alternatives to primary to secondary education. This study aims to analyze the distribution of educational resources, equality of education quality, and access to scholarships for children of migrant workers in Sabah. Using John Rawls' Social Justice theory approach, this research is expected to contribute in evaluating and recommending more inclusive and equitable education policies for migrant workers' children in border areas. Keyword: Children of migrant workers, Community Learning Center, Education Optimization